Topologies of the Virtual. Spaces, Images, and Bodies in Early Modern Choir Stalls (Cinéma & Cie. Film and Media Studies Journal, 2023)
Early Modern choir stalls are spaces within spaces, they separate spheres such as public and restricted, profane and holy, as well as open and closed. Members of the convents perform their daily devotions here and are assigned to respective seats. They are installed, according to the name of the place “stalla”. The inlaid decoration on each seat reiterates the specific spatial and religious formation. This article wants to explore how choir stalls immerse their users and viewers in pictorial and religious environments.
Keywords: Media Archaeology; Early Modernity; Topologies; Trompe-l’oeil; Embedding